The Impact of Handedness, Sex, and Cognitive Abilities on Left–Right Discrimination: A Behavioral Study - Constant, Martin; Mellet, Emmanuel (Frontiers in Psychology, 2018)
The present study examined the relationship between Left-Right Discrimination (LRD) performance and handedness, sex and cognitive abilities. In total, 31 men and 35 women - with a balanced ratio of left-and right-handers - completed the Bergen Left-Right Discrimination Test. We found an advantage of left-handers in both identifying left hands and in verifying "left" propositions. A sex effect was also found, as women had an overall higher error rate than men, and increasing difficulty impacted their reaction time more than it did for men. Moreover, sex interacted with handedness and manual preference strength. A negative correlation of LRD reaction time with visuospatial and verbal long-term memory was found independently of sex, providing new insights into the relationship between cognitive skills and performance on LRD.